Low-frequency noise behaviors of quasi-two-dimensional electron systems based on complex oxide heterostructures - Kim, Youngmin; Kim, Doyeop; Mo, Sang Hyeon; Ryou, Sang Hyeok; Lee, Jung Woo; Eom, Kitae; Rhim, Jun Won; Lee, Hyungwoo (Current Applied Physics, 2024)
We report the low-frequency noise behaviors in quasi-two-dimensional (quasi-2D) electron systems based on complex oxide heterostructures. First, the surface 2D electron gas (2DEG) on SrTiO3 (STO) exhibits the 1/fα-type current power spectral density (PSD) with α∼1.39. The non-unity exponent α indicates the discrepancy between the depth distributions of electrons and oxygen vacancies in the STO substrate. Second, the amorphous LaAlO3/KTaO3 (LAO/KTO) interface, another quasi-2D electron system, shows Lorentzian components of PSD at a high-frequency region around 1 kHz, implying that the amorphous overlayer can provide additional shallow charge-trapping sites to the quasi-2D electrons in the crystalline KTO substrate. Lastly, ultrathin SrRuO3 (SRO) film grown on STO substrate exhibits the Lorentzian components of PSD at a low-frequency region around 200 Hz. The slight suppression of the fast charge trapping is attributed to the intrinsic band bending at the interface between film and substrate. These results will provide a guideline for understanding the defect-induced charge trapping and the relevant electron dynamics in the quasi-2D electron systems as well as the oxide-based electronic materials in general.
Keywords: 2D electron gas; 2D electron system; Charge-trapping; Complex oxides; Low-Frequency Noise; Noise behavior; Oxide heterostructures; Quasi-2d; Quasi-two-dimensional electron systems; SrTiO 3; 2D electron gas; Charge trapping; Low-frequency noise; Oxide heterostructures